H. J. EYSENCK (1916-1997) AND THE PSYCHOLOGY OF INTELLIGENCE - Pelechano, Vicente (Anales de Psicología / Annals of Psychology)
The death of H. J. Eysenck represents the missing of the most important european psychologist since Wundt. Eysenck began to study human intelligence later in his scientific development however from the beginning shown a hard position: intelligence is basically one in line with the theory of Spearman, a natural, biological and genetically based phenomenon. In this field Eysenck has defend a theoretical position very near to information processing theory and has offered a theory on creativity in which personality and intelligence have been joined. The coherence of this position in relationhips to his general theory of personal functioning and structure, summary of data and theoretical alternatives are revisited. Here is defended that human intelligence, in contemporary and complex western society represents basically a socially based concept and nearer to a multiple competence theory than a natural-biologically one. Background and illustrations from this perspective follow.